Life as Moving Towards the Other - Lindseth, Anders (Journal of Comparative Social Work, 2014)
The ethics of Knud Ejler Løgstrup (1905-1981) is relation ethics. It raises the question of how we can do justice to the life of the Other as it is laid in our hands. In this paper, I start out with an ethical dilemma, clarify the concepts of decision ethics and relation ethics, and I then present the ethics of Løgstrup understood as relation ethics. Lastly, I discuss the important question – within the fields of social work, health care, psychotherapy and pedagogical practices – of how we can meet people in need of our help in an ethical way.